2008
DOI: 10.1093/toxsci/kfn056
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Mitochondrial Dysfunction and Cytotoxicity of Nefazodone, Trazodone, and Buspirone

Abstract: Mitochondrial toxicity is increasingly implicated in a host of drug-induced organ toxicities, including hepatotoxicity. Nefazodone was withdrawn from the U.S. market in 2004 due to hepatotoxicity. Accordingly, we evaluated nefazodone, another triazolopyridine trazodone, plus the azaspirodecanedione buspirone, for cytotoxicity and effects on mitochondrial function. In accord with its clinical disposition, nefazodone was the most toxic compound of the three, trazodone had relatively modest effects, whereas buspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
146
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(169 citation statements)
references
References 31 publications
17
146
1
Order By: Relevance
“…31 Recent studies showed that citalopram and escitalopram decreased the activity of respiratory chain complexes. 32 Dykens et al 33 showed that antidepressants induce mitochondrial dysfunction and cytotoxicity. In this context, a recent study showed that tricyclic antidepressants can modulate mitochondrial functions indirectly through a decrease in nitric oxide production.…”
Section: Discussionmentioning
confidence: 99%
“…31 Recent studies showed that citalopram and escitalopram decreased the activity of respiratory chain complexes. 32 Dykens et al 33 showed that antidepressants induce mitochondrial dysfunction and cytotoxicity. In this context, a recent study showed that tricyclic antidepressants can modulate mitochondrial functions indirectly through a decrease in nitric oxide production.…”
Section: Discussionmentioning
confidence: 99%
“…The same work showed that NEF treatment resulted in inhibition of both bile acid transport, via the bile salt export pump (BSEP) present in membrane vesicles, and the canalicular transport in cultured human hepatocytes (Kostrubsky et al, 2006). NEF was also shown to directly impair hepatic mitochondrial function through inhibition of OXPHOS complexes, particularly complex I (Dykens et al, 2008;Nadanaciva et al, 2007). Although mitochondrial dysfunction seems to be a major player behind NEF hepatotoxicity, there are only a few reports describing the possible mechanisms involved (Dykens et al, 2008;Kim et al, 2012;Swiss et al, 2013;Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…NEF was also shown to directly impair hepatic mitochondrial function through inhibition of OXPHOS complexes, particularly complex I (Dykens et al, 2008;Nadanaciva et al, 2007). Although mitochondrial dysfunction seems to be a major player behind NEF hepatotoxicity, there are only a few reports describing the possible mechanisms involved (Dykens et al, 2008;Kim et al, 2012;Swiss et al, 2013;Xu et al, 2008). Dykens et al, reported that NEF treatment resulted in a decreased mitochondrial transmembrane electric potential (DJ m ), a marked reduction in the intracellular levels of reduced glutathione, and a rise in the levels of reactive oxygen species (ROS) in primary cultures of human hepatocytes (Dykens et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations